2018
DOI: 10.1155/2018/3048532
|View full text |Cite|
|
Sign up to set email alerts
|

Formononetin Administration Ameliorates Dextran Sulfate Sodium-Induced Acute Colitis by Inhibiting NLRP3 Inflammasome Signaling Pathway

Abstract: Formononetin is a kind of isoflavone compound and has been reported to possess anti-inflammatory properties. In this present study, we aimed to explore the protective effects of formononetin on dextran sulfate sodium- (DSS-) induced acute colitis. By intraperitoneal injection of formononetin in mice, the disease severity of colitis was attenuated in a dose-dependent manner, mainly manifesting as relieved clinical symptoms of colitis, mitigated colonic epithelial cell injury, and upregulations of colonic tight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 41 publications
(50 reference statements)
2
47
0
Order By: Relevance
“…carnosol is i.p. injection and lots of other molecules, such as MCC950 and Formononetin, are also used in this application route 22,[70][71][72][73] .Intraperitoneal administration of carnosol with 200 mg/kg daily for 5 days has no effect on liver weight 73 . Furthermore, we confirmed that carnosol is well tolerated in mice when administered intraperitoneally at 120 mg/kg daily for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…carnosol is i.p. injection and lots of other molecules, such as MCC950 and Formononetin, are also used in this application route 22,[70][71][72][73] .Intraperitoneal administration of carnosol with 200 mg/kg daily for 5 days has no effect on liver weight 73 . Furthermore, we confirmed that carnosol is well tolerated in mice when administered intraperitoneally at 120 mg/kg daily for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Several specific inhibitors, such as MCC950, CY‐09, arglabin, and glyburide, have been recently developed or identified to target NLRP3 inflammasome inhibition . The application of these specific NLRP3 inflammasome inhibitors has demonstrated therapeutic effects in various inflammatory disease mouse models, including models of myocardial infarction, fulminant hepatitis, steatohepatitis, lupus nephritis, atherosclerosis, Alzheimer's disease, brain injury, inflammatory bowel diseases, acute colitis, and carcinoma In allergic diseases, the application of MCC950 reduces skin and airway inflammation in mouse models of allergic dermatitis and asthma . More recently, 2 studies have shown that the targeted inhibition of NLRP3 inflammasomes with a specific inhibitor decreased IL‐1β and TH2 cytokines and inhibited HDM‐induced AHR and steroid‐resistant asthma in a mouse model .…”
Section: Discussionmentioning
confidence: 99%
“…As we discussed above, the NLRP3 inflammasome is mainly produced in innate immunity cells, thus triggering the cascade immune and inflammatory reaction through the secretion of two pro-inflammatory cytokines including IL-1β and IL-18. As a result, the NLRP3 inflammasome is highly involved in the onset and development of various kinds of diseases, including cardiovascular diseases (myocardial ischemia/infarction, atherosclerosis, and hypertension), metabolic disorders (obesity, diabetes, and metabolic syndrome), digestive diseases (inflammatory bowel disease), renal diseases and CNS diseases ( Chen et al, 2017 ; Kammoun et al, 2018 ; Martinez et al, 2018 ; Nasoohi et al, 2018 ; Sharma et al, 2018 ; Wu et al, 2018b ; Yuan et al, 2018 ). In addition, it has been demonstrated that the polymorphism of the NLRP3 genes may lead to the occurrence of some congenital disorders in patients and animal models ( Lewis et al, 2011 ; Kuemmerle-Deschner et al, 2017 ; Landmann and Walker, 2017 ).…”
Section: Nlrp3 Inflammasome In Cns Disordersmentioning
confidence: 99%